Reading scripture with the church fathers - Hall, Christopher A. (Downers Grove, IL IVP, 1998)
Includes bibliographical references and index.
Keywords: Bible -- criticism, interpretation, etc. -- history -- early church, ca.30-600.; Fathers of the church